Estudio de prefactibilidad para la instalación de una planta procesadora de enlatados de jurel (Trachurus murphyi) de tipo grated - Medina Rivero, Juan Diego (2018)
During the last years in the world has been generated a trend of increased consumptions of healthy products, such is the case of fish , thanks to the properties of their meat low in calories and rich in protein has managed to become an essential product for this trend. This trend allowed us to find a market, which led to the study of horse mackerel. In the first place, the product was defined in its three levels, as well as the CIUU, the respective tariff heading and the marketing policies and distribution channels. To determine the demand for the project, historical demand had to be analyzed through the imports and exports of canned fish in recent years.